A low PAPR performance with new segmentation schemes of partial transmit sequence for OFDM systems - A. Jawhar, Yasir; Shah, Nor Shahida; A. Taher, Montadar; N. Ramli, Khairun; S. Ahmed, Mustafa; Abdulhasan, R. (Institute of Advanced Studies in Education (IASE), 2017)
Despite the fact that OFDM has numerous features, the high peak-to-average power ratio (PAPR) deems one of the challenging disadvantages face by the system in the real applications. The high PAPR limits the OFDM signal efficiency on the transmitter side. Thus many PAPR alleviation approaches have been suggested in the past. Partial transmit sequences (PTS) has been accounted as one of the successful procedures for decreasing the high PAPR; with the consideration that the computational complexity of the PTS method regarded high relatively. Moreover, improving the PAPR mitigation performance of the PTS algorithm relies upon the number of the partitioned subblocks, the number of the phase rotation vectors, and the kind of the segmentation scheme utilized. This article presents new segmentation schemes to enhance the PAPR mitigation execution without further intricacy on the system. Adjacent shifting segmentation scheme (Ad-Sh-PTS) and rows exchange of interleaving segmentation schemes (IL-Ex-PTS) are proposed depending on the two well-known segmentation schemes of adjacent partition PTS (Ad-PTS) and interleaving partition PTS (IL-PTS). The simulation demonstrates that the suggested algorithms can accomplish mitigation in PAPR preferable compared to the traditional schemes, Ad-PTS and IL-PTS schemes.